2018
DOI: 10.1080/15384047.2018.1529093
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor Suberoylanilide Hydroxamic Acid (SAHA) as a therapeutic agent in rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is an aggressive childhood sarcoma with two distinct subtypes, embryonal (ERMS) and alveolar (ARMS) histologies. More effective treatment is needed to improve outcomes, beyond conventional cytotoxic chemotherapy. The pan-histone deacetylase inhibitor, Suberoylanilide Hydroxamic Acid (SAHA), has shown promising efficacy in limited preclinical studies. We used a panel of human ERMS and ARMS cell lines and xenografts to evaluate the effects of SAHA as a therapeutic agent in both RMS subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…We hereby demonstrate that treatment of young AG04431 HDFs with SAHA induces cell proliferation arrest (as detected by a decreased staining of Ki-67 in these cells), concomitant with an increased protein abundance of p21 WAF-1 , an increase in the proportion of SA-βgal positive cells, a decreased expression of Lamin B1 and an increased expression and secretion of several SASP factors. These results concur with the induction of biomarkers of senescence, including growth arrest, following SAHA treatment in human leukemia cell lines [ 39 ], in rhabdomyosarcoma cell lines [ 40 ] and in human colon cancer cell line HCT116 [ 41 ]. As p21 WAF-1 protein abundance is increased at 24 hr after SAHA treatment, it could be involved in the early proliferative arrest.…”
Section: Discussionsupporting
confidence: 80%
“…We hereby demonstrate that treatment of young AG04431 HDFs with SAHA induces cell proliferation arrest (as detected by a decreased staining of Ki-67 in these cells), concomitant with an increased protein abundance of p21 WAF-1 , an increase in the proportion of SA-βgal positive cells, a decreased expression of Lamin B1 and an increased expression and secretion of several SASP factors. These results concur with the induction of biomarkers of senescence, including growth arrest, following SAHA treatment in human leukemia cell lines [ 39 ], in rhabdomyosarcoma cell lines [ 40 ] and in human colon cancer cell line HCT116 [ 41 ]. As p21 WAF-1 protein abundance is increased at 24 hr after SAHA treatment, it could be involved in the early proliferative arrest.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, we observed that SAHA but not TSA promoted features of cellular senescence in HCC cells. In some tumors such as rhabdomyosarcoma [44] and urothelial carcinoma [45], HDAC inhibition has been shown to affect senescence. Fan.…”
Section: Discussionmentioning
confidence: 99%
“…Different HDACis have been found to induce senescence; however, the clinical implication is not yet fully understood. In rhabdomyosarcoma, vorinostat was shown to mediate senescent features and increase the expression of the cell cycle inhibitors p21 and p27 [ 113 ]. Urothelial cancer cells revealed senescence morphologies upon treatment with unselective HDACis [ 114 ].…”
Section: Molecular Mechanisms Of Hdaci-promoted Anticancer Effectsmentioning
confidence: 99%